Bright bluish-green emitting Cu(i) complexes exhibiting efficient thermally activated delayed fluorescence. Issue 15 (19th March 2021) - Huang, Chun-Hua; Yang, Mingxue; Chen, Xu-Lin; Lu, Can-Zhong
Abstract : Three strongly emissive Cu(i ) complexes exhibiting bright bluish-green thermally activated delayed fluorescence in the solid state with high quantum yield up to 91% were synthesized and characterized. Abstract : Three strongly emissive Cu(i ) complexes [Cu( t Bupzmpy)(POP)]BF4 (1 ), [Cu(Phpzmpy)(POP)]BF4 (2 ) and [Cu(Adpzmpy)(POP)]BF4 (3 ) ( t Bupzmpy = 2-(5-( tert -butyl)-1 H -pyrazol-3-yl)-6-methylpyridine, Phpzmpy = 2-methyl-6-(5-phenyl-1 H -pyrazol-3-yl)pyridine, Adpzmpy = 2-(5-((3 R, 5 R )-adamantan-1-yl)-1 H -pyrazol-3-yl)-6-methylpyridine, and POP = bis[2-(diphenylphosphino)phenyl]ether) were synthesized and characterized. These complexes exhibit bright bluish-green photoluminescence in the solid state with quantum yields of 91% (1 ), 71% (2 ) and 77% (3 ) and lifetimes of 13.4 μs (1 ), 32.9 μs (2 ) and 34.1 μs (3 ) at room temperature. The results of theoretical calculations, coupled with the temperature dependence of the spectroscopic properties and emission decay behaviors, reveal that the title Cu(i ) complexes emit efficient thermally activated delayed fluorescence (TADF) from excited states involving metal-to-ligand charge transfer (MLCT) transitions and ligand-to-ligand charge transfer (LLCT) transitions. The emissive-state characteristics and emission properties of the investigated Cu(i ) complexes were tuned effectively by changing the steric and electronic structures of the diimine ligands.